2022
DOI: 10.3390/w14091407
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Modulates the Effects of Short-Term Heat, Drought and Combined Stresses after Anthesis on Photosynthesis, Nitrogen Metabolism, Yield, and Water and Nitrogen Use Efficiency of Wheat

Abstract: More frequent and more intense heat waves and greater drought stress will occur in the future climate environment. Short-term extreme heat and drought stress often occur simultaneously after winter wheat anthesis, which has become the major constraint threatening future wheat yield. In this study, short-term heat, drought and their combination stress were applied to wheat plants after anthesis, and all wheat plants were restored to the outdoor normal temperature and full watering after stress treatment. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Compared to the CF regime, we also observed an increase in F v /F m , Φ PSII , and qP of CID at the heading stage (Table 2), and a positive correlation with biomass and yield (Figure 8), in agreement with previous studies [55]. The CID regime created alternating wet and dry conditions in rice fields, where the soil transformed between aerobic and anaerobic environments, stimulating the microbial decomposition of straw.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to the CF regime, we also observed an increase in F v /F m , Φ PSII , and qP of CID at the heading stage (Table 2), and a positive correlation with biomass and yield (Figure 8), in agreement with previous studies [55]. The CID regime created alternating wet and dry conditions in rice fields, where the soil transformed between aerobic and anaerobic environments, stimulating the microbial decomposition of straw.…”
Section: Discussionsupporting
confidence: 91%
“…Plant phenolic compounds respond to drought stress in various ways depending on factors such as the exposure time and volume of water given to the plant. An increased total content of flavonoids, phenolics, and multiple polyphenolics and increased radical scavenging activity were observed in plants under drought stress. , Caffeic acid levels, for example, do not follow any pattern. The decrease in the protein content can be attributed to a reduction in protein synthesis or an increased rate of protein degradation. , These findings indicate that heavy metal levels are essential in shielding plants from drought stress (Figure ).…”
Section: Discussionmentioning
confidence: 86%
“…Secondary metabolites are organic products that aid the plant with protection, defense, reproduction, and adaptation to these adverse environments . Flavonoids and phenolic compounds play a critical role in the defense against drought stress. , In crops, drought stress and its interaction with growth and photosynthesis are associated with changes in nitrogen (N) and protein status. , Phenolic compounds are known to be produced in higher amounts under stress conditions as these play a significant role in the growth and development of plants . During their growth and development, plants absorb essential microelements such as copper (Cu), zinc (Zn), and manganese (Mn), as well as some nonessential metal elements like cadmium (Cd), lead (Pb), and mercury (Hg). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen content in the plant measured as nitrate, ammonium ions, and proteins. Besides performing basic roles in plants, its metabolism is also very crucial for heat tolerance because it increases the osmolyte content and antioxidant enzyme activity (Ru et al, 2022 ). Studies have also shown their role in promoting the HSP production (Heckathorn et al, 1996 ).…”
Section: Physiological Aspects and Cellular Functions Under Heat Stressmentioning
confidence: 99%